Meme un Oiseau a Beson de Son Nid - Chansou, Christine; Trintignant, Vincent (France, 2012)
A documentary regarding forced evictions in Cambodia, Every Bird Needs a Nest reveals the Cambodian government’s concession of residential land to commercial companies while a group of women, led by Tep Vanny, protest being forced out of their homes even under threats and intimidation.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films